Optical Coherence Tomography in Patients with Chiari I Malformation. (22nd February 2015) - Figus, Michele; Posarelli, Chiara; Nasini, Francesco; Perrini, Paolo; Miccoli, Mario; Baggiani, Angelo; Ferreras, Antonio; Nardi, Marco
Abstract : Background/Aims . To evaluate optic nerve head with spectral domain optical coherence tomography (OCT) in patients with Chiari I malformation (CMI) compared to healthy controls. Methods . Cross-sectional study. OCT of the optic nerve head of 22 patients with CMI and 22 healthy controls was quantitatively analyzed. The healthy controls were matched for age and sex with the study population. Mean retinal nerve fiber layer (RNFL) thickness was calculated for both eyes; the mean thickness value was also registered for each quadrant and for each subfield of the four quadrants. Results . CMI patients showed a reduction of the RNFL thickness in both eyes. This reduction was more statistically significant (P < 0.05 ) for the inferior quadrant in the right eye and in each quadrant than nasal one in the left eye. Conclusion . A distress of the retinal nerve fibers could explain the observed reduction of the RNFL thickness in patients with CMI; in our series the reduction of the RNFL thickness seems lower when CMI is associated with syringomyelia.